Atomistic simulation of primary microstructure formation in metals during crystallization from the melt - Vladimir V. Dremov; Pavel V. Chirkov; Roman M. Kichigin; Alexey V. Karavaev; Elena B. Cherepetskaya; Vladimir V. Cheverikin; Vladimir S. Dub; Ivan A. Ivanov; Sergey V. Salikhov (Scientific Reports)
Abstract Additive manufacturing of metallic parts by Selective Laser Melting (SLM) implies high temperature gradients and small volume of the melt bath. These conditions make the process scales close to those available for state-of-the-art massively parallel atomistic simulations. In the paper, the microscopic mechanisms responsible for the formation of primary microstructure during molten metal solidification are investigated using classical molecular dynamics (CMD). The 316L austenitic stainless steel with face centred cubic lattice, which is widely used in industry including SLM applications was chosen as a material for the CMD simulations. It was shown that solidified material inherits substrate defects and catches new ones, which interact with the solidification front thus producing the primary microstructure. Peculiarities of solidification in different crystallographic directions and solidification front interaction with grain boundaries and newly produced defects (mostly twin boundaries) as well as their formation are under study. Resulting microstructures of virtual samples are compared with those of real samples produced by SLM and analysed by the electron backscatter diffraction (EBSD) method. The comparison shows similarities of EBSD and CMD sample patterns and evidences for the capability of the large-scale atomistic simulations to reproduce main features of the microstructures formed in the metallic SLM additive production.